The Paths of Oblivion and Political Rituals during the Government of National Conciliation in Costa Rica (1958-1962) - Ugalde Quesada, Alexia (Revista de historia., 2021)
This article establishes that during the government of Mario Echandi Jiménez (1958-1962) a process of national conciliation took place. This process is analyzed through the implementation of what we called «compensation measures» and «political rituals of inclusion», which endorsed the 1948 civil war`s losers. For example, the return of Rafael Angel Calderón Guardia and the declaration of a second amnesty for all those linked to the war. As a conclusion, the national conciliation process was also favored by the intensification of the opposition movement to the Somoza dictatorship, as this generated a new configuration of the «enemy» characterizing him as a foreigner, which in turn promoted internal unity.